Investigate the Influencing Factors of Industrial Design Platform Demand: From the Perspective of Emotional Interaction - Zhang, Chenxiao; Yang, Qin; Tong, Lei; Zhou, Rong (Frontiers in Psychology, 2022)
With the deep integration of industries brought by industrial interconnection, users' design needs also show a trend of diversification and individuation. The cross of multiple service resources and information barriers of multiple organizations in the traditional design supply chain lead to the lag of design resource recommendation time, which makes the design enterprises (units) face the problem of reduced efficiency of information resource flow in the industrial interconnection business. Based on the user demand text, the grounded theory is used to excavate deeply, so as to analyze the influential factors of realizing the rational recommendation platform of dynamic multi-service resources in the design supply chain, and the relationship among the factors is analyzed by using the explanatory structure model. The results show that government and market are the most basic factors leading the development of industrial design service platform, and universities play a key role in it. This study not only provides a theoretical reference for understanding the influence mechanism of industrial design service platform, but also provides a direction for promoting the development of industrial design service platform in the future.